Electrospray performance of interacting multi-capillary emitters in a linear array. (23rd January 2018) - Kumar, V; Srivastava, A; Shanbhogue, K M; Ingersol, S; Sen, A K
Abstract: Here, we report electrospray performance of multiple emitters (of internal diameter 200 µ m) arranged in a linear (inline) array. For a fixed flow rate Q, at higher voltages V a, multi-jet mode is observed, which leads to a rapid increase in the spray current ( I ∼ V a ) as compared to the single cone-jet case ( I ∼ V a 0.8 ). A theoretical model is presented that predicts (within 10% of experimental data) the divergence of sprays g ( x ) issued from a pair of interacting emitters due to the mutual Columbic interaction of space charges. The variation of onset voltage V o and spray current I with spacing between the emitters p is studied and it is found that V o ∼ p − 0.2 and I ∼ p 0.8 . The effect of the flow rate Q, voltage V and number of emitters   n   on the spray current I is investigated and it is found that I ∼ Q 0.5, I ∼ V a 0.8 and I ∼ n . The present work provides insight regarding the behavior of interacting sprays in an inline configuration and could be significant in the design of multiple emitter systems for electrospray applications.